CS-OFDMA a new wireless CDD physical layer scheme. - Lee, William C.Y (IEEE Communications magazine)
A proposed new innovative wireless CDD physical layer scheme for 4G called CS-OFDMA is introduced. Code spreading uses a set of smart codes with its meritorious properties, which can eliminate multipath and multiuser interferences. The same number of smart codes applied repeatedly in each subcarrier of OFDMA is used to increase the number of traffic channels. It takes advantage of attributes of both CDMA and OFDMA toward a simpler and more spectrally efficient system applied in a CDD system.